TYPES AND WAYS OF SPEAKING ASSESSMENT USED BY ENGLISH TEACHERS - Dwi Warry Octaviana (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2024)
Many English teachers have been trying to expand CLT in their classrooms. However, although they are interested in CLT, communicative assessment has received little attention. So, they do not assess students' oral proficiency from the perspective of language use and communication. Thus, there is a contradiction between their communicative language teaching and their assessments of speaking which do not reflect authentic oral interaction. Therefore, this study aimed to identify the types and ways of speaking assessment used by English teachers. In acquiring the data, this study used qualitative descriptive approach. The data needed were gained through two qualitative data collection instruments: a questionnaire and semi-structured interviews. In relation to the data gained, the data findings show that there are several types of such non-authentic speaking assessment tasks used by the English teachers. Furthermore, there are certain ways of speaking assessment used by English teachers. It can be categorized into three main categories: knowledge (giving explanation), comprehension (drawing conclusion), and performance (conversation).